Comparison of hemodynamic effects of lidocaine, prilocaine and mepivacaine solutions without vasoconstrictor in hypertensive patients - Bahadir Ezmek; Ahmet Arslan; Cagri Delilbasi; Kemal Sencift (University of São Paulo, 2010)
OBJECTIVE: Local anesthetic solutions with vasoconstrictors are not contraindicated in hypertensive patients, but due to their hemodynamic effects, local anesthetics without vasoconstrictors are mainly preferred by the clinicians. The aim of this study was to compare hemodynamic effects of three different local anesthetics without vasoconstrictors during tooth extraction in hypertensive patients. MATERIAL AND METHODS: Sixty-five mandibular molars and premolars were extracted in 60 hypertensive patients (29 females and 31 males; mean age: 66.95 ± 10.87 years; range: 38 to 86 years old). Inferior alveolar and buccal nerve blocks were performed with 2% lidocaine hydrochloride (HCl), 2% prilocaine HCl or 3% mepivacaine HCl without vasoconstrictor. Hemodynamic parameters namely systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), heart rate (HR), saturation rate (SR), rate pressure product (RPP) and pressure rate quotient (PRQ) were investigated before and at different intervals after anesthetic injection. RESULTS: The hemodynamic effects of the three agents were similar to each other, although some significance was observed for DBP, MAP, RPP and PRQ values in the lidocaine, prilocaine and mepivacaine groups. CONCLUSION: Lidocaine, prilocaine and mepivacaine solutions without vasoconstrictor can be safely used in hypertensive patients. It is advisable that dental practitioners select anesthetic solutions for hypertensive patients considering their cardiovascular effects in order to provide patient comfort and safety.